Expressive Speech Acts in the Film Keluarga Cemara by Yandy Laurens - Safira, Merlina Elsa; Pattiasina, Petrus Jacob; Somelok, Grace (Universitas Pattimura, 2023)
This study aims to describe expressive speech acts in the film Keluarga Cemara by Yandy Laurens. This type of research is descriptive qualitative. The data collection techniques used in this research are listening techniques tapp, ing techniques, and note-taking techniques. Researchers conducted data analysis covering four stages: data collection, data reduction, data presentation and conclusions. The results of this study functioned in expressing gratitude, congratulating, giving praise, expressing apology, expressing anger, and blaming